Social Capital Formation, Internet Usage and Economic Growth in Australia: Evidence from Time Series Data - Mohammad Salahuddin; Clem Tisdell; Lorelle Burton; Khorshed Alam (International Journal of Economics and Financial Issues, 2015)
This study estimates the short- and long-run effects of social capital and Internet usage on economic growth using annual time series macro-data for Australia for the period of 1985-2013. DF-GLS unit root and Zivots and Andrew structural break tests are conducted to assess the stationarity of all the series. Hansen-Gregory and ARDL bounds tests confirm a cointegrating relationship among the variables. ARDL estimates indicate a significant long-run positive relationship between economic growth and Internet usage. No significant relationship is found between economic growth and social capital in both the short- and the long-run. However, the interaction term of Internet usage and social capital has a significant positive association with economic growth both in the short- and long-run. The short-run relationship between economic growth and Internet usage is insignificant. A bidirectional causal link exists between Internet usage and economic growth and between the interaction variable and economic growth. Unidirectional causality runs from Internet usage to the interaction variable. No causal relation is found between social capital and economic growth. The findings are also supported by applications of a different econometric method, namely DOLS estimation. The positive interaction effect of Internet use and social capital on economic growth supports the recently raised view that Australia should take into account social capital formation in its digital divide policy.